A new tetragonal superhard carbon allotrope with unusual stress-strain behavior. (1st June 2023) - Zhang, Qian; Pang, Zhibo; Li, Yi; Cheng, Yifan; Liu, Mingsheng; Xiong, Mei; Jia, Shaopei; Li, Qisong; Gao, Yufei; Mu, Yunchao; Huang, Quan
Abstract: We identified a carbon allotrope with tetragonal symmetry ( P 42 / nnm, 12 atoms/cell), termed TC12. Unusual tensile behavior characterized by an enormous deformation was observed, leading to a phase transition from superhard TC12 to metallic T6 carbon. This could be related to planar recovery of the C2 atom during stretching of twisted six-membered rings along the crystal direction [100]. The tensile limit of TC12 along the [100] crystal direction is up to 62.5%, corresponding to the tensile strength of 129.96 GPa. The phonon dispersion spectra and elastic constant verified its dynamical and mechanical stabilities. TC12 is a metastable 3D carbon allotrope possessing remarkable mechanical properties: bulk modulus of 339 GPa together with hardness of 56.8 GPa. Electronic structure prediction showed that semiconductor TC12 has an indirect bandgap of 2.247 eV. The findings establish a unique type of carbon phase, which is suggested as a potential material for electronic and machining applications. Highlights: We identified a carbon allotrope TC12 ) with tetragonal symmetry ( P 42 / nnm ) based on first principle calculations. TC12 exhibited somewhat atypical non-continuous strain-stress behavior when stretching. After extending 7.5% along the [100] crystal direction, it transforms into three-dimensional metallic carbon T6. The electronic structure shows that TC12 is an indirect band-gap insulator with a bandgap of 2.247 eV° .